1979
DOI: 10.1029/ja084ia11p06489
|View full text |Cite
|
Sign up to set email alerts
|

On the orientation of the polar cap electric field

Abstract: Using realistic models of the ionospheric conductivity and the field‐aligned currents, we have determined how the distribution of the electric field in the polar cap ionosphere is controlled by the day‐night contrast in conductivity and by the relative strengths of the region 1 and region 2 field‐aligned currents. The sunward directed conductivity gradient acts to set up a space charge in the polar cap which crowds the equipotentials toward the dawn sector for current sources of both region 1 and region 2 pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…This has been a result of ignoring ionospheric dynamo effects (Kamide and Vickrey, 1983). However, there are reasons to expect seasonal variations of the high latitude electric field; to name a few: the ionospheric conductivity gradient as caused by the day-night difference of the solar photoionization (e.g., Wolf, 1970;Atkinson and Hutchison, 1978), the ionospheric conductivity gradient across the auroral zone (Yasuhara et al, 1983), the change of the relative strength of the region I and II field-aligned currents (Nopper and Carovillano, 1979), and the change of the tilt between the magnetic pole axis and the Sun-Earth line, which modifies the projection of IMF on GSM coordinates (de la Beaujardie´re et al, 1991). Crooker and Rich (1993) suggested summerwinter differences in the potential due to merging of the open field lines in the lobes with the solar wind.…”
Section: Seasonal Dependencementioning
confidence: 98%
“…This has been a result of ignoring ionospheric dynamo effects (Kamide and Vickrey, 1983). However, there are reasons to expect seasonal variations of the high latitude electric field; to name a few: the ionospheric conductivity gradient as caused by the day-night difference of the solar photoionization (e.g., Wolf, 1970;Atkinson and Hutchison, 1978), the ionospheric conductivity gradient across the auroral zone (Yasuhara et al, 1983), the change of the relative strength of the region I and II field-aligned currents (Nopper and Carovillano, 1979), and the change of the tilt between the magnetic pole axis and the Sun-Earth line, which modifies the projection of IMF on GSM coordinates (de la Beaujardie´re et al, 1991). Crooker and Rich (1993) suggested summerwinter differences in the potential due to merging of the open field lines in the lobes with the solar wind.…”
Section: Seasonal Dependencementioning
confidence: 98%
“…Thus there is discrepancy between our observations and earlier observation by de la Beaujardiere et al, [1991 ] and Ruohoniemi and Greenwald [1995] In this section, we discuss the mechanisms which can cause the -2 hours clockwise (the 2 hrs curvature effect is excluded) rotation of convection orientation from winter to summer. Nopper and Carovillano [1979], Yashuhara et al, [1983] and Blomberg and Marklund [1988] have shown the effect of conductivity and field aligned currents (in terms of ratio of the Region 1 to Region 2 currents) in the rotation of the convection pattern. The polar cap electric field is rotated -60 ø, 40 ø, 10 ø east of noon for the ratios 2, 1.5, 1 between Region 1 and Region 2 field aligned currents respectively [Nopper and Carovillano, 1979].…”
Section: Observationsmentioning
confidence: 99%
“…Using magnetic data from 28 northern hemisphere observatories for the interval 1330-1400 UT on March 22, 1964 (see Nishida's [1968] Figure 7), which represents one of the typical DP 2 examples (A. Nishida, personal communication, 1979), we calculated the magnetic potential V by the technique outlined by Kroehl and Richmond [ 1980]. The internal component of V, due to induced earth currents, was removed by the crude approximation that it is equivalent to the magnetic effects that would be induced at the surface of a perfectly conducting layer at a depth of 600 km [see Price, 1967]. The equivalent current function q4 shown in Figure 3a, was then obtained by extrapolation of V to 110 km and appropriate transformation of the spherical harmonic coefficients (see Chapman and Barrels, p.…”
Section: Ionosphericmentioning
confidence: 99%